Possible Efficacy of Vedolizumab, an Anti-α4β7 Integrin Antibody, in Palmoplantar Pustulosis - Hitoshi Terui; Rintaro Moroi; Atsushi Masamune; Setsuya Aiba; Kenshi Yamasaki (Karger Publishers, 2023)
Palmoplantar pustulosis (PPP) is a chronic skin inflammatory disease in which blisters and pustules repeatedly develop on palms and soles. PPP is often refractory to topical therapy, oral therapy, phototherapy, and biologics that are usually applied for PPP. We report a patient with PPP improved by vedolizumab (anti-α4β7 integrin antibody) treatment for ulcerative colitis, suggesting the possibility of a new molecular target for PPP therapy.